Improving Student Activities and Learning Outcomes through the Problem-Based Learning Model in Chemistry Learning - P. C. Dini; R. Hidayah; S. Nurlatifah (Journal of Science Education Research, 2023)
This study aims to describe the increase in activities and learning outcomes of students on the mole concept material by applying a problem-based learning model. The subjects in this study were students of class X-E at SMA Negeri 1 Rengel. This study used a type of classroom action research. The research instruments used are observation sheets of student activities and test sheets of learning outcomes. The learning tools used in this study are teaching modules with Student Worksheets on the mole concept material. The methods used to collect data in this study are observation and test methods. The results of the study showed that (1) In each cycle, the activities of relevant students had a more significant percentage than the activities of irrelevant students, namely 88.89% in cycle I and 94.59% in cycle II; (2) Student learning outcomes have reached classical completeness of 86.84% in cycle II, and the average N-gain score obtained by students in cycle I is 0.63, while in cycle II is 0.89. The percentage of students who obtained N-gain on high and medium criteria in cycle II increased from cycle I, namely 84.21% and 15.79%. Based on the study's results, learning using a problem-based model can improve student activities and learning outcomes.